Profile of Cesarean Sections Since the BPJS Era - Mohd. Andalas; Cut R. Maharani; Raudhatul Jannah; Siti Harisah; Muhammad Haekal; Ichsan (Indonesian Journal of Obstetrics and Gynecology, 2020)
Objective: to find out the profile of caesarean section in dr. Zainoel Abidin Hospital since the BPJS era.